(untitled) (Research, Society and Development, 2023)
The present paper aims to present a literature review on the subject of dentoalveolar trauma (DDT), from etiological factors to treatment. A literature review was performed by searching the SciELO, PubMed and LILACS databases with the keywords "Dental Trauma", "Dental Avulsion" and "Dental Care" from 2005 to 2022, and 15 articles were selected in Portuguese and English. TDA are injuries caused by impacts on soft tissues, teeth and/or hard tissues inside or outside the mouth, usually occurring spontaneously, accidentally and unexpectedly, which require emergency care. The most affected age group corresponds to children and adolescents, and the most affected teeth are the anterior teeth. TDA encompasses several types of lesions with variable severity and prognosis. The correct professional approach, preferably with immediate care, is of utmost importance because it reflects on the prognosis of the case. The TDA is present in clinical dental practice representing a public health problem, so it is of utmost importance the training of dental professionals on the subject.